Measuring waste in Malaysia: a neglected approach / Mei Lim - Mei, Lim (Faculty of Architechture , Planning & Surveying, 2011)
The aim of this paper is to explore why Full Cost Accounting (FCA) has not been adopted by solid waste management (SWM) in Malaysia. A case study methodology is used for the exploratory research undertaken in this study. Thematic analysis is used and it reveals that lack of regulation is a central barrier to the adoption of FCA. FCA emerges as a supported but little understood concept among participants who are environmentally sensitive. The findings are theorised against Roger's (1995) innovation-adoption model and revealed that two types of innovations relations to adoption of FCA in SWM in Malaysia. One was the behavioural change aimed at better SWM. The other was the awareness of the need for FCA.